Distribution and Expression of Programmed Death Ligand -1 (PD-L1) in Non-Small Cell Carcinomas of the Lung in a Tertiary Care Centre in South India - Sheba S K JACOB (Federation of Turkish Pathology Societies, 2021)
Objective: Non-small cell lung carcinomas often present at an advanced stage with a grim prognosis. Immune checkpoint (ICP) inhibitors have drastically changed the scenario, and the response to ICP inhibitors is determined by analyzing the expression of PD-L1 by immunohistochemistry. PD-L1 immunohistochemistry helps in optimizing the treatment, and avoiding unnecessary exposure of patients to the toxic effects of the drugs that are ineffective and expensive in non-expressing tumors. This study was conducted to assess the prevalence of the expression of PD-L1 in non-small cell carcinomas of the lung diagnosed at our institution, which is a tertiary care center in South India. Material and Method: The PD-L1 immunohistochemistry of 77 cases of non-small cell carcinomas of the lung diagnosed over a period of two years were reviewed and analyzed (2018-2020). All tissues were fixed in 10% neutral buffered formalin and processed by standard methods, and the Ventana SP263 clone was used. Results: Seventy-seven cases of non-small cell lung carcinomas were reviewed and studied for (PD-L1) expression. 35/77 (45%) of the cases had PD-L1 expression (≥ 1%) and 14 (18 %) had high (PD-L1) expression. Also there was a male preponderance of 2.3:1. High PD-L1 expression was seen mostly in patients above 60 years of age and was usually associated with high tumor grade. Conclusion: It is important to assess PD-L1 expression in non-small cell carcinomas of patients especially with higher tumor grade and older age groups that they may benefit from immune checkpoint inhibitor therapy.